On the Dini–Hadamard-like coderivative of the difference of two single-valued mappings - Baias, Alina Ramona; Kerekes, Delia Maria (Rendiconti del Circolo matematico di Palermo, 2021)
In this paper we obtain a difference rule for the Dini–Hadamard-like coderivative involving spongiously Lipschitz and strongly spongiously continuous mappings. We also provide a short overview of all the spongious continuity notions, emphasizing the connections between them.